A scoping review of post-earthquake healthcare for vulnerable groups of the 2023 Turkey-Syria earthquakes - Joseph Kimuli Balikuddembe; Jan D. Reinhardt; Ghanbari Vahid; Baofeng Di (BMC, 2024)
Abstract Background Identifying healthcare services and also strengthening the healthcare systems to effectively deliver them in the aftermath of large-scale disasters like the 2023 Turkey-Syria earthquakes, especially for vulnerable groups cannot be emphasized enough. This study aimed at identifying the interventions undertaken or proposed for addressing the health needs or challenges of vulnerable groups immediately after the occurrence of the 2023 Turkey-Syria earthquakes, as well as for prioritizing their healthcare service delivery in the post-Turkey-Syria earthquake. Methods In this scoping review compiled with the five steps of the Arksey and O'Malley framework, five databases, including PubMed, Science Direct, Web of Science, OVID, and Google Scholar, were searched for studies published between March and April 2023 in line with the eligibility criteria. Interventions for enhancing post-earthquake healthcare services (PEHS) were grouped into seven (7) categories, adopted from previous guidelines and studies. Each one was assigned a default score of a value equal to one (1), which, in the end, was summed up. Results Of the 115 total records initially screened, 29 articles were eligible for review. Different interventions they reported either undertaken or proposed to address the healthcare needs and challenges, especially faced by the most vulnerable groups in the aftermath of the Turkey-Syria earthquakes, were categorized into 7 PEHS. They were ranked with their scores as follows: humanitarian health relief (25); medical care (17); mental health and psychosocial support (10); health promotion, education, and awareness (9); disease surveillance and prevention (7); disability rehabilitation (7); and sexual and reproductive health (5). Conclusion Since there are no proper guidelines or recommendations about the specific or most significant PEHS to prioritize for vulnerable groups after the occurrence of large-scale earthquakes, this scoping review provides some insights that can help inform healthcare service delivery and prioritization for vulnerable groups in the post-2023 Turkey-Syria earthquakes and other similar disasters.